The Forgiveness Process for Students Who Were Victims of Bullying at SMP Negeri 1 Mangunreja - Cucu Arumsari; Dewang Sulistiana; Hilma Fauziah G (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2025)
This study aims to understand the process of forgiveness among students who have experienced bullying at SMP Negeri 1 Mangunreja. Forgiveness is an essential aspect of emotional recovery, which helps reduce anger and hatred while rebuilding the individual’s psychological balance. This research employed a qualitative narrative approach to explore the subjective experiences of students in forgiving their bullies. Data were collected through in-depth interviews with a primary participant (the bullying victim) and two supporting informants: a guidance and counseling teacher and a close friend. The data analysis involved three stages: data reduction, data display, and conclusion drawing. The findings reveal that the process of forgiveness occurs through four main stages: (1) emotional wounds and psychological impacts of bullying; (2) self-reflection and awareness of the meaning of forgiveness; (3) social support as a factor of recovery; and (4) forgiveness as a form of growth and inner peace. These stages describe a complex emotional journey toward acceptance and self-healing. Forgiveness emerges as an act of self-empowerment influenced by social support, spiritual values, and counseling guidance. This study contributes to the field of guidance and counseling by highlighting forgiveness-based counseling as an effective intervention strategy for students who experience bullying.